(untitled) (Research, Society and Development, 2025)
Photobiomodulation (PBM) is an emerging technique used as an adjunct therapy in the management of acne vulgaris. The aim of this narrative literature review is to present the potential use of photobiomodulation in the treatment of acne vulgaris. This method involves the use of low-intensity light sources, such as LEDs or lasers, which are applied directly to the skin to stimulate biological processes and promote cell regeneration. Acne vulgaris is a common skin condition that affects millions of people, significantly impacting their quality of life due to its clinical manifestations, including pustules, comedones, and inflammatory nodules. Studies have shown that PBM can reduce inflammation and the number of acne lesions by modulating sebaceous gland activity and decreasing the proliferation of Propionibacterium acnes bacteria. Additionally, PBM stimulates collagen production, contributing to the healing of lesions. PBM treatments are generally well tolerated, with few reported side effects, making it a viable and effective alternative for patients seeking options beyond traditional pharmacological treatments. Thus, photobiomodulation emerges as a promising approach, complementing conventional therapeutic regimens and offering significant benefits in controlling and improving acne vulgaris conditions.